Edible plant-derived essential oils synergistically enhance the Th1, Th2 and anti-inflammatory cytokines in neonatal cord blood monocytic cell line - Swagatika Dash (Taylor & Francis Group, 2018)
Edible medicinal plants Curcuma longa, Kaempferia galanga and Zingiber officinale are considered to be suitable for pregnant mother and neonates. Their essential oils are claimed to have therapeutic effects, yet its immunomodulatory activities need to be investigated. To validate the immunomodulatory effect, cord blood monocyte cells (CBMCs) treated with different concentrations of essential oils ranging from 0 to 40 µg/ml. K. galanga oil at 40 µg/ml concentrations upregulated IFN-γ at 49.23 pg/ml, while C. longa oil downregulated the IL-10 at 10.45 pg/ml showing immunostimulant activity on CBMCs. However, Z. officinale oil showed no significant result at any concentration. K. galanga and C. longa oils also showed an increase in lymphocyte proliferation in a dose-dependent manner. The present study was aimed to evaluate the immunomodulatory potentialities of essential oils which will attract the interest of researchers and pharmaceutical industries for clinical studies and other applications in the therapy of diseases related to neonatal infections.